HYGIENIC ESTIMATION OF NUTRITION OF SCHOOLCHILDREN IN ORENBURG REGION (IN THE CONTEXT OF EXPERIMENTAL PROJECT OF NUTRITION ORGANIZATION) - T.I. Burtseva; S.V. Notova; N.V. Malysheva; Zh.Yu. Gorelova; A.V. Skal'nyi; O.I. Burlutskaya (Вопросы современной педиатрии, 2008)
Hygienic peculiarities of nutrition of schoolchildren in 2–3 forms were analyzed in this article. Decreased consumption of biologically valuable food staffs, misbalanced receipt of basic nutrients and insufficient use of some micronutrients (iodine, zinc, vitamins d, с and в1, folat) were discovered. Comparison between nutrition of schoolchildren in city and in village showed that there's a significant differences between using of most of nutrients. Key words: schoolchildren, nutrition, macronutrients, micronutrients.